Լեզվական ինքնատիպություն՝ գեղեցիկ ձևի մեջ - Հակոբյան, Կ․ Ա․
Статья посвящена изучению языковых средств произведений поэта -литературоведа С.Ханяна - автора 15 сборников стихотворений и поэм. В своих произведениях поэт умело использовал выразительные возможности армянского языка, обогащая свою речь чистыми и светлыми оттенками. Это явление в поэзии С. Ханяна в своё время заметил знаменитый писатель Мкртич Армен. В поэзии С.Ханяна использованы эпитеты, повторы, сопоставления, метафоры, сравнения, которые показывают его лексическое богатство. Поэтическое мышление С. Ханяна близко к народному, поэтому в его стихах встречаются выражения, звучащие как пословицы. The article is dedicated to the study of the linguistic means, used in the works of the poet and literary critic Socrat Khanian. He is the author of 15 collections of poems and verses. In his poems he used expressive means of the Armenian language, which enriched his poetry with pure and light nuances. His verses are full of epithets, repetitions, similies, metaphors. This phenomenon was noted by the famous writer Mcrteech Armen. Khanian's poetical thinking is close to the Armenian folklore in his poems we find many expressions sounding like proverbs.
Keywords: Գրական գործիչներ; Գրական վերլուծություն